Towards Continuous, Non-Invasive Assessment of Ventricular Function and Hemodynamics: Wearable Ballistocardiography - Wiens, Andrew (IEEE J Biomed Health Inform, 2014)
Ballistocardiography, the measurement of the reaction forces of the body to cardiac ejection of blood, is one of the few techniques available for unobtrusively assessing the mechanical aspects of cardiovascular health outside of clinical settings. Recently, multiple experimental studies involving healthy subjects and subjects with various cardiovascular diseases have demonstrated that the ballistocardiogram (BCG) signal can be used to trend cardiac output, contractility, and beat-by-beat ventricular function for arrhythmias. The majority of these studies have been performed with “fixed” BCG instrumentation—such as weighing scales or chairs—rather than wearable measurements. Enabling wearable, and thus continuous, recording of BCG signals would greatly expand the capabilities of the technique; however, BCG signals measured using wearable devices are morphologically dissimilar to measurements from “fixed” instruments, precluding the analysis and interpretation techniques from one domain to be applied to the other. In particular, the time intervals between the electrocardiogram (ECG) and BCG – namely, the R-J interval, a surrogate for measuring contractility changes – are significantly different for the accelerometer compared to a “fixed” BCG measurement. This paper addresses this need for quantitatively normalizing wearable BCG measurement to “fixed” measurements with a systematic experimental approach. With these methods, the same analysis and interpretation techniques developed over the past decade for “fixed” BCG measurement can be successfully translated to wearable measurements.